2007
DOI: 10.1136/bjsm.2007.036228
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of anabolic steroids in sport, physical activity and as a drug of abuse: an analysis of the scientific literature and areas of research

Abstract: It was concluded that there has been an upward trend in the number of research projects. The sources used complemented one another, as 78.04% of the documents retrieved were unique to one source. The productivity ranking was headed by sports medicine journals, followed by journals of chemistry, physiology, endocrinology and substance abuse. Besides sporting activities, the most important research clusters were those connected with bodybuilding and with youth groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
8

Year Published

2008
2008
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
14
0
8
Order By: Relevance
“…But, over time, a wide use of drugs has also been observed in women. In fact, the 2015 European Drug Report of the European Monitoring Centre for Drugs and Drug Addiction indicated that approximately one in four users entering treatment are women and one out of every five drug-related-deaths is female (Buccelli et al, 2016;Calatayud, Alcaide, Zurian, & Benavent, 2007;Striegel, Ulrich, & Simon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…But, over time, a wide use of drugs has also been observed in women. In fact, the 2015 European Drug Report of the European Monitoring Centre for Drugs and Drug Addiction indicated that approximately one in four users entering treatment are women and one out of every five drug-related-deaths is female (Buccelli et al, 2016;Calatayud, Alcaide, Zurian, & Benavent, 2007;Striegel, Ulrich, & Simon, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Por todo ello, la motivación de los adolescentes influye y desempeña una labor relevante sobre las conductas de consumo (Jiménez, Cervelló, García-Calvo, Santos-Rosa & Iglesias, 2007;Rubak, Sandbaek, Lauritzen & Christensen, 2005), por lo que resulta fundamental atender a ella para en la prevención e intervención del consumo en aras de una mayor adherencia y disfrute de la actividad físico-deportiva (Agulló-Calatayud, 2008;González-Alcaide, Valderrama-Zurián, y Aleixandre-Benavent, 2008;Bartík, 2012;Hodge, Hargreaves, Gerrard & Lonsdale, 2013;Pérez-Milena, Olmedilla, Mesa, Jiménez, Martínez & Pérez-Milena, 2010;Prieto, 2015;Roessler, 2009).…”
Section: Discussionunclassified
“…Several studies have documented both the increase in the amount consumed and in the variety of new formulations. However, in the last fifteen years, patterns of recreational steroid use have emerged outside the sphere of competitive sport (Agulló et al 2008;Petrocelli et al 2008;Breivík et al 2009;Bojsen-Møller and Christiansen 2010;Rosenberg and Rodríguez 2010;Christiansen and Bojsen-Møller 2012;Agulló-Calatayud 2013).…”
Section: Introductionmentioning
confidence: 97%